The Effect of Service Quality, Customer Experience, and Customer Satisfaction on Customer Loyalty in the Service Industry in Indonesia - Harlen Silalahi; Joni Wilson Sitopu; Mislan Sihite (North Press, 2024)
This study investigates the effects of service quality, customer experience, and customer satisfaction on customer loyalty in the service industry in Indonesia. Using a quantitative approach, data were collected from 120 respondents through a structured questionnaire based on a 5-point Likert scale. The data were analyzed using SPSS version 26, with reliability, correlation, and multiple regression analysis performed. The results indicate that service quality, customer experience, and customer satisfaction all significantly positively affect customer loyalty, with customer satisfaction emerging as the strongest predictor. The findings suggest that improving service quality and customer experience are essential for enhancing customer satisfaction and fostering loyalty in the Indonesian service industry. This study provides practical insights for service industry practitioners on retaining customers and building long-term loyalty in a competitive market.